Disentangling two causes of biased probability judgment: Cognitive skills and perception of randomness - Kai Duttle (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
This experimental study investigates the interaction of two influential factors of biased probability judgments. Results provide new insights on the preconditions for an application of either the gambler's fallacy or its exact opponent, the hot hand fallacy. The first factor is cognitive ability, measured in a cognitive reflection test. The second one is the level of perceived randomness in the observed outcomes. Probability judgments are found to vary significantly across salience of randomness treatments as well as across subgroups with high or low cognitive abilities. Like in previous research, subjects with higher cognitive skills are more likely to engage the gambler's fallacy, yet only if perception of sequential randomness is low. In a setting where randomness is very salient the exact opposite can be observed. Similarly surprising insights are revealed when controlling for cognitive abilities in the analysis of salience treatments. Past results are only confirmed for a subgroup with lower cognitive skills, while their peers' beliefs are completely opposite. – – Diese experimentelle Studie untersucht die Interaktion zweier Einflussfaktoren auf fehlerhafte Wahrscheinlichkeitsschätzungen. Die Ergebnisse geben Einblick in die Voraussetzungen für eine Verhaltensanwendung der sogenannten Gambler's Fallacy einerseits, oder aber dem genauen Gegenstück, der Hot Hand Fallacy. Der erste Faktor ist die kognitive Fähigkeit, welche in einem Cognitive Reflection Test gemessen wird. Der zweite ist das Ausmaß der wahrgenommenen Zufälligkeit in den beobachteten Ausgängen. Wahrscheinlichkeitsschätzungen variieren signifikant sowohl über die Zufallswahrnehmungs-Treatments als auch über Gruppen mit guten respektive schlechteren kognitiven Fähigkeiten. Wie in früheren Studien wenden Teilnehmer mit hohen kognitiven Fähigkeiten eher die Gambler's Fallacy an, jedoch ausschließlich bei geringer Wahrnehmung sequentieller Zufälligkeit. Ist diese jedoch sehr offensichtlich, kann das genau gegenteilige Verhalten beobachtet werden. Ähnlich überraschende Ergebnisse bringt eine Analyse der Auswirkungen von Variationen in der Zufallswahrnehmung bei gleichzeitiger Kontrolle des Einflusses kognitiver Fähigkeiten. Ergebnisse bisheriger Forschung können lediglich für eine Gruppe mit schlechteren Fähigkeiten repliziert werden. Die Schätzungen der Teilnehmer mit besseren Fähigkeiten sind komplett gegensätzlich.
Keywords: C91; D84; J24; 330; law of small numbers; gambler's fallacy; hot hand effect; cognitive reflection test